The Effect of Openness to Experience on Trust Behavior: The Moderating Role of Situational Strength - Hendarsjah, Hidajat (Humaniora: Journal of Indonesia Culture and Society, 2023)
The research aimed to integrate how trusting behavior was formed by an interaction between individual personality traits and situational context. Trust game protocol and a series of personality trait questionnaires were utilized to generate the data. A moderated regression with categorical variables was established to test the hypothesis of whether a player’s role or situational strength moderated the relationship between players’ trait and their corresponding trusting behavior. Regression results showed that situational strength moderated the U-shaped relationship between openness to experience and trusting behavior, such that the U-shaped relationship was more pronounced in weak situations. The research tested the hypotheses in the trust game setting to isolate the moderating role of weak and strong situations. In future research, it is necessary to present both weak and strong situations in a real organizational setting. The research offers insight into how individuals, from lower to higher openness to experience developed the trusting behavior to explore information to enhance their knowledge of an economic decision-making situation. The U-shaped relationship implies the course of the knowledge enhancement; first, by exploring the internal belief (thus it makes lower trust) to understand the situation, and second, by putting more trust in others to reduce the need for instantaneous compensation because of an enhanced expectation that commitment would be honored in the future.